Microstructural Analysis of Concrete Using Cow Bone Ash for Alkali-Silica Reaction (ASR) Suppression - Ariyo, Adanikin; Falade, Funsho; Olutaiwo, Adewale (Journal of Casting & Materials Engineering, 2020)
Concrete pavements are prone to microstructural changes and deterioration when exposed to Alkali-Silica Reaction (ASR). ASR results in strength reduction, cracking, spalling and other defects in the concrete if left unchecked. Supplementary Cementitious Materials (SCMs) such as Cow Bone Ash (CBA) however can be used to improve concrete performance, hence its use in this study. Concrete samples were prepared at replacement levels of 0%, 5%, 10%, 15%, 20% and 30% of cement with Cow Bone Ash. The concrete samples were then subjected to petrographic and Scanning Electron Microscopy (SEM) analysis. Petrographic examination shows that the minimal and least amount of ASR gels and micro cracking were observed at 15% CBA replacement of cement in the concrete samples. Scanning Electron Microscopy (SEM) analysis shows that changes in the elemental composition of the concrete samples is related to the effect of CBA which enhances adhesion in the concrete. SEM analysis show that, in general, the change in microstructure in the concrete was mainly due to the change in the arrangement of the C-H-S compounds. The microstructure analysis indicates that CBA in concrete influences the densification of the concrete at the transition zone, resulting in a much lower porosity. This results in the concrete having a tightly bound layer that repels ingress of water and thereby inhibiting cracks and gel formation as water is a contributing factor to the ASR in concrete.